Analysis of corrosion scales formed on steel at high temperatures in hydrocarbons containing model naphthenic acids and sulfur compounds. (22nd January 2015) - Jin, Peng; Nesic, Srdjan; Wolf, H. Alan
<x xml:space="preserve">Abstract</x> Corrosive naphthenic acids and sulfur compounds in crude oils present a major challenge for refineries from a corrosion perspective. Although it is accepted that some sulfur compounds may form protective FeS scales on the metal surface and deter corrosion, attempting to correlate the characteristics of FeS scale with its protective properties has not been successful. Given the complex chemical compositions of real crudes, model sulfur compound and model naphthenic acids were used to mimic the corrosion by crude fractions in the present study. The iron sulfide scale formed by the model sulfur/acid compounds was challenged by naphthenic acids under high‐velocity conditions to examine its protectiveness against corrosion. Moreover, the scale was analyzed with transmission electron microscope/energy dispersive X‐ray spectroscopy technique, and a layer of iron oxide formed on the 5Cr steel was found when naphthenic acids were present in the solution. The iron oxide layer appeared to be important for maintaining protection against naphthenic acid corrosion, and further analysis revealed that it was composed of magnetite. Copyright © 2015 John Wiley & Sons, Ltd.